2003
DOI: 10.4049/jimmunol.171.10.5380
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Macrophage Apoptosis Contributes to Pneumococcal Clearance in a Resolving Model of Pulmonary Infection

Abstract: The role of alveolar macrophages (AM) in host defense against pulmonary infection has been difficult to establish using in vivo models. This may reflect a reliance on models of fulminant infection. To establish a unique model of resolving infection, with which to address the function of AM, C57BL/6 mice received low-dose intratracheal administration of pneumococci. Administration of low doses of pneumococci produced a resolving model of pulmonary infection characterized by clearance of bacteria without feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
249
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(259 citation statements)
references
References 68 publications
7
249
0
2
Order By: Relevance
“…We have demonstrated that macrophage apoptosis is a feature of in-vitro challenge of macrophages to S. pneumoniae and also occurs in vivo [30,36]. It is observed with both human and murine macrophages.…”
Section: Apoptosis-associated Killingmentioning
confidence: 79%
See 2 more Smart Citations
“…We have demonstrated that macrophage apoptosis is a feature of in-vitro challenge of macrophages to S. pneumoniae and also occurs in vivo [30,36]. It is observed with both human and murine macrophages.…”
Section: Apoptosis-associated Killingmentioning
confidence: 79%
“…Using defined inocula of S. pneumoniae, depletion of alveolar macrophages with liposomes containing clodronate or mice with genetic modifications that alter intracellular killing of bacteria (as discussed below), we have demonstrated that mice with decreased numbers of alveolar macrophages, or with alveolar macrophages of reduced microbicidal capacity, are more susceptible to development of pneumonia and that the threshold inoculum required to generate pneumonia is reduced significantly [30,[32][33][34]. The capacity of macrophages to clear bacteria is finite, and even in wildtype mice the inoculum can be increased to a 'tippingpoint' beyond which alveolar macrophages no longer control the bacteria in the airway [30,31]. At these higher inocula alveolar macrophage depletion does not alter bacterial clearance because the macrophage capacity for bacterial clearance is already saturated.…”
Section: Alveolar Macrophages Role In Host Defence Against Pulmonary mentioning
confidence: 99%
See 1 more Smart Citation
“…The commonest cause of community-acquired pneumonia in this population is infection with Streptococcus pneumoniae, the pneumococcus (2). The successful resolution of bacterial pneumonia is dependent on a coordinated immune response with neutrophil recruitment when resident defenses are overwhelmed (3). After clearance of bacteria, a resolution phase, mediated by apoptosis of recruited cells and clearance by phagocytosis, prevents tissue injury by activated neutrophils (4).…”
mentioning
confidence: 99%
“…Protection against the extracellular bacteria requires efficient recruitment of neutrophils and macrophages to the site of infection (199,200). Recent research established a role for type I IFNs in interfering with this innate defense mechanism.…”
Section: Role Of Type I Ifns In Bacterial and Viral Coinfectionmentioning
confidence: 99%